Maintaining strategic ambiguity for protection: struggles over opacity, equivocality and absurdity around the Sicilian Mafia - Cappellaro, G; Compagni, A; Vaara, E (Academy of Management, 2020)
In spite of an increasing interest in ambiguity, our knowledge of how organizations maintain strategic ambiguity to protect themselves from public scrutiny is still in its infancy. Through an in-depth historical study of the Sicilian Mafia between 1963 and 2018, we develop a model of strategic ambiguity maintenance. We focus on three struggles between the Mafia and state representatives and show how they centered on different types of ambiguity: ambiguity as opacity, equivocality and absurdity. We elaborate on the strategies enacted by the Mafia and the responses by state representatives and their implications for ambiguity over time. The main contribution of our paper is that it advances understanding of the maintenance of strategic ambiguity by organizations that need to protect themselves from public scrutiny. More specifically, it enriches understanding of the key process dynamics, the type of struggles, and the discursive and non-discursive strategies employed in the process. Our analysis also extends research on clandestine organizations and illuminates the relationship between (strategic) ambiguity and secrecy.